Long-term Prolonged-release Tacrolimus-based Immunosuppression in De Novo Kidney Transplant Recipients: 5-Y Prospective Follow-up of Patients in the ADVANCE Study. Issue 3 (8th February 2023) - Pernin, Vincent; Glyda, Maciej; Viklický, Ondrej; Lõhmus, Aleksander; Wennberg, Lars; Witzke, Oliver; von Zur-Mühlen, Bengt; Anaokar, Swapneel; Hurst, Martin; Kazeem, Gbenga; Undre, Nasrullah; Kuypers, Dirk R.J.
Abstract : Background: Although prolonged-release tacrolimus (PR-T) is widely approved for posttransplantation immunosuppression in kidney recipients, large-scale studies are required to assess long-term outcomes. We present follow-up data from the Advagraf-based Immunosuppression Regimen Examining New Onset Diabetes Mellitus in Kidney Transplant Recipients (ADVANCE) trial, in which kidney transplant patients (KTPs) received corticosteroid minimization with PR-T. Methods: ADVANCE was a 24-wk, randomized, open-label, phase-4 study. De novo KTPs received PR-T with basiliximab and mycophenolate mofetil and were randomized to receive an intraoperative corticosteroid bolus plus tapered corticosteroids until day 10 (arm 1) or an intraoperative corticosteroid bolus (arm 2). In this 5-y, noninterventional follow-up, patients received maintenance immunosuppression according to standard practice. The primary endpoint was graft survival (Kaplan-Meier). Secondary endpoints included patient survival, biopsy-confirmed acute rejection-free survival, and estimated glomerular filtration rate (4-variable modification of diet in renal disease). Results: Follow-up study included 1125 patients. Overall graft survival at 1 and 5 y posttransplantation was 93.8% and 88.1%, respectively, and was similar between treatment arms. At 1 and 5 y, patient survival was 97.8% and 94.4%, respectively. Five-year graft and patient survival rates in KTPs who remained on PR-T were 91.5% and 98.2%, respectively. Cox proportional hazards analysis demonstrated similar risk of graft loss and death between treatment arms. Five-year biopsy-confirmed acute rejection-free survival was 84.1%. Mean ± standard deviation values of estimated glomerular filtration rate were 52.7 ± 19.5 and 51.1 ± 22.4 mL/min/1.73 m 2 at 1 and 5 y, respectively. Fifty adverse drug reactions were recorded, probably tacrolimus-related in 12 patients (1.5%). Conclusions: Graft survival and patient survival (overall and for KTPs who remained on PR-T) were numerically high and similar between treatment arms at 5 y posttransplantation. Abstract :